2018
DOI: 10.1039/c7cp08631h
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent magnetic and inductive heating properties of Fe3O4 nanoparticles: scaling laws across the superparamagnetic size

Abstract: An efficient heat activating mediator with an enhanced specific absorption rate (SAR) value is attained via control of the iron oxide (Fe3O4) nanoparticle size from 3 to 32 nm. Monodispersed Fe3O4 nanoparticles are synthesized via a seed-less thermolysis technique using oleylamine and oleic acid as the multifunctionalizing agents (surfactant, solvent and reducing agent). The inductive heating properties as a function of particle size reveal a strong increase in the SAR values with increasing particle size up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 66 publications
8
78
1
Order By: Relevance
“…Later, Xu et al found that by changing the heating conditions, and ratios of oleylamine and oleic acid, the size of Fe 3 O 4 NPs can be tuned from 14 to 100 nm [67]. Recently, oleylamine was used as a multitasking agent, acting as a solvent, and reducing and surface functionalizing agents, to prepare monodispersed Fe 3 O 4 NPs with a reasonably large magnetization value [68,69,70,71]. The experiment confirms that the presence of excess amount of oleylamine offers an adequately strong reductive environment for the Fe-precursor and leads to the formation of Fe 3 O 4 NPs at a reasonably low temperature of 240 °C.…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Xu et al found that by changing the heating conditions, and ratios of oleylamine and oleic acid, the size of Fe 3 O 4 NPs can be tuned from 14 to 100 nm [67]. Recently, oleylamine was used as a multitasking agent, acting as a solvent, and reducing and surface functionalizing agents, to prepare monodispersed Fe 3 O 4 NPs with a reasonably large magnetization value [68,69,70,71]. The experiment confirms that the presence of excess amount of oleylamine offers an adequately strong reductive environment for the Fe-precursor and leads to the formation of Fe 3 O 4 NPs at a reasonably low temperature of 240 °C.…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
“…The experiment confirms that the presence of excess amount of oleylamine offers an adequately strong reductive environment for the Fe-precursor and leads to the formation of Fe 3 O 4 NPs at a reasonably low temperature of 240 °C. Figure 6A shows the representative TEM micrographs of monodispersed Fe 3 O 4 nanoparticles of size ranging from 6 to 24 nm, prepared by thermolysis of Iron(III) acetylacetonate in oleic acid and oleylamine [71]. These synthesis methods were also extended to formulate MFe 2 O 4 (M = Co, Ni, and Mn) NPs.…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
“…In order to deliver nanoparticles with these characteristics, their composition, size, and shape should be optimized. For instance, magnetite nanoparticles with sizes within the range of 4–27 nm [ 10 , 11 , 12 ] and cuboctahedral versus cubic have been demonstrated to show the highest specific absorption rate (SAR) values for magnetic hyperthermia [ 13 ]. On the other hand, and to be able to combine magnetic hyperthermia with targeted drug delivery, the magnetic nanoparticles should be easily functionalized with different moieties, e.g., a drug and a probe, and to this goal, they should provide a chemical surface pattern mediating the binding for these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Iron(III) oxides show remarkable magnetic properties, both for fundamental investigations and practical applications. The magnetic properties of these materials have been shown to depend on their size, shape, and microstructure [11][12][13][14][15][16]. In particular, iron(III) oxides are an attractive group of materials with a wide range of magnetic properties, from antiferromagnetic, superparamagnetic and weak ferromagnetic to ferrimagnetic [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%